2019
DOI: 10.3390/polym11010092
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Hydroxyapatite Loaded with Resveratrol in Colloidal Suspension Improves Viability, Metabolic Activity and Mitochondrial Potential in Human Adipose-Derived Mesenchymal Stromal Stem Cells (hASCs)

Abstract: In response to the demand for new multifunctional materials characterized by high biocompatibility, hydrogel (HG) nanocomposites as a platform for bioactive compound delivery have been developed and fabricated. A specific crosslinking/copolymerization chemistry was used to construct hydrogels with a controlled network organization. The hydrogels were prepared using 3,6-anhydro-α-l-galacto-β-d-galactan (galactose hydrogel) together with resveratrol (trans-3,5,4′-trihydroxystilbene) and calcium hydroxyapatite na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…It was also found that nHAp clumped into smaller regions of the hydrogel matrix (c,d). A similar observation has been made in our previous research [ 24 ]. We noticed that nHAp-modified hydrogel increases the proliferative activity and viability of human multipotent stromal cells (hASCs), as well as reduces markers of oxidative stress.…”
Section: Resultssupporting
confidence: 91%
“…It was also found that nHAp clumped into smaller regions of the hydrogel matrix (c,d). A similar observation has been made in our previous research [ 24 ]. We noticed that nHAp-modified hydrogel increases the proliferative activity and viability of human multipotent stromal cells (hASCs), as well as reduces markers of oxidative stress.…”
Section: Resultssupporting
confidence: 91%
“…The reaction conditions were described previously. 35,37,38 The list of primers is presented in Supplementary Material. The average fold change in the gene expression was calculated using the RQ MAX algorithm, ie scaled to the sample having the lowest expression and converted into log2 scale as described previously.…”
Section: Cytocompatibility Of Zro 2 Ald Coatingsmentioning
confidence: 99%
“…Before the qPCR, samples were diluted 10-fold using DEPC water. The reaction was performed as described above (Section 2.8) and using protocol described previously [43]. The maximum relative quantification (RQ max ) of gene expression was calculated in relation to a snU6 gene using 2 −∆∆Ct algorithm.…”
Section: Methodsmentioning
confidence: 99%